Once upon a Sesame Street Christmas [videorecording (DVD)] (Warner Home Video, 2017)
Travel back to the nineteenth century, when humans and monsters didn't get along, as Elmo and his friends learn how Christmas and the holiday spirit came to Sesame Street!